Revitalisasi Pendidikan Islam sebagai Upaya Kebangkitan Ummat: Analisis Pola Pendidikan Generasi Shalahuddin al-Ayyubi - Fatimah, Siti; Nurrohim, Ahmad (Universitas Mathla'ul Anwar Banten, 2025)
This paper examines the revitalization of Islamic education as a strategic initiative for the resurgence of the Muslim ummah, with a particular emphasis on the educational practices during the period of Salahuddin Al-Ayyubi. Adopting the framework proposed by Dr. Majid Irsan Al-Kilani, the study investigates the educational models applied in Islamic institutions of that era, which were instrumental in producing a generation marked by strong spirituality, intellectual excellence, and capable leadership. By incorporating insights from contemporary academic literature, this research demonstrates how historical educational strategies can be reinterpreted and adapted within modern educational systems to nurture individuals who are intellectually proficient, ethically sound, and actively involved in the ummah’s revival. The paper concludes by offering actionable recommendations for applying these educational models in current Islamic educational Keywords: Islamic education, revival of the ummah, Salahuddin Al-Ayyubi, historical education model, contemporary adaptation settings.